2019
DOI: 10.1371/journal.pntd.0007124
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of a locally produced rapid diagnostic test for early detection of cholera in Bangladesh

Abstract: Background Cholera remains a substantial health burden in Asia and Africa particularly in resource poor settings. The standard procedures to identify the etiological organism V . cholerae are isolation from microbiological culture from stool as well as Polymerase Chain Reaction (PCR). Both the processes are highly lab oriented, labor extensive, time consuming, and expensive. In an effort to control for outbreaks and epidemics; an effective, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…However, we do not rule out the possibilities of other four culture-positive isolates as Vibrio spp., without screening them with other primers available for the detection of Vibrio spp. Vibrio is the major cause of diarrhea in many countries of the world including Bangladesh [6,33]. A study conducted in Nepal showed that variation in geographical locations or primer used greatly influence the occurrence and detection of various Vibrio spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not rule out the possibilities of other four culture-positive isolates as Vibrio spp., without screening them with other primers available for the detection of Vibrio spp. Vibrio is the major cause of diarrhea in many countries of the world including Bangladesh [6,33]. A study conducted in Nepal showed that variation in geographical locations or primer used greatly influence the occurrence and detection of various Vibrio spp.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, V. cholerae is considered as the most devastating agent [5]. Across the world, an estimated 1.3 billion people are at risk of cholera; of which Bangladesh jointly constitutes the largest share of the population at risk [6]. Recently, it has been reported that around 66 million people in Bangladesh are at risk for cholera with an incidence of about 1.64 per thousand people [7].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, the South Sudan outbreak indicated that the Crystal VC RDT, when used with a simple step of enrichment in alkaline peptone water, demonstrated performance similar to that of culture [12]. RDTs are thus fast, practical, and effective tests for large-scale epidemics where containment of the infection from the beginning is critical [13]. While stool culture is still the gold standard for diagnosing cholera, the time required to obtain results, combined with deficiencies in laboratory infrastructure, sample transportation, and staff training, can significantly delay detection and control actions [12].…”
Section: Discussionmentioning
confidence: 99%
“…The commonly reported public health problems among the FDMNs are acute watery diarrhea, measles, acute respiratory infections, diphtheria, malaria, other infectious diseases as well as malnutrition [10]. Cholera is endemic in Bangladesh [11] and it is prevalent in Cox's Bazar [12]. The aim of the study was to evaluate the immune responses to OCV among the healthy FDMNs in Bangladesh and to compare the immune response of the FDMN participants with data of the vibriocidal responses seen in adults and children in an earlier vaccination study carried out in the Mirpur urban area in Dhaka.…”
Section: Introductionmentioning
confidence: 99%